Evolution in health and disease - Stearns, S. C. (Stephen C.), 1946-; Koella, Jacob C. (Oxford : Oxford University Press, 2008)
This work explores and analyses the ways in which our ancient genes contend with, and influence, modern human life. It offers coverage of the points of contact between evolutionary biology and medical science.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Medical genetics; Human evolution; Diseases -- Causes and theories of causation